Zinc uptake in the Basidiomycota: Characterization of zinc transporters in Ustilago maydis. (1st January 2019) - Martha-Paz, Adriana M.; Eide, David; Mendoza-Cózatl, David; Castro-Guerrero, Norma A.; Aréchiga-Carvajal, Elva T.
Abstract: At present, the planet faces a change in the composition and bioavailability of nutrients. Zinc deficiency is a widespread problem throughout the world. It is imperative to understand the mechanisms that organisms use to adapt to the deficiency of this micronutrient. In the Ascomycetes fungi, the ZIP family of proteins is one of the most important for zinc transport and includes high affinity Zrt1p and low zinc affinity Zrt2p transporters. After identification and characterization of ZRT1/ZRT2-like genes in Ustilago maydis we conclude that they encode for high and low zinc affinity transporters, with no apparent iron transport activity. These conclusions were supported by the gene deletion in Ustilago and the functional characterization of ZRT1/ZRT2-like genes by measuring the intracellular zinc content over a range of zinc availability. The functional complementation of the S. cerevisiae ZRT1Δ ZRT2Δ mutant with U. maydis genes supports this as well. U. maydis ZRT2 gene, was found to be regulated by pH through Rim101 pathway, thus providing novel insights into how this Basidiomycota fungus can adapt to different levels of Zn availability.